2016
DOI: 10.4314/star.v4i3.7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of growing media, sowing depth, and hot water treatment on seed germination and seedling biomass of <i>Acacia senegal</i> (L) wild

Abstract: To optimize seedling production for reforestation of degraded dryland with study was conducted on the effect of boiled water treatment, growing media, sowing depth on seed germination and seedling growth of A. senegal forest soil and sand soil), boiled water seed pre seeds as control and three sowing depths (2, 4 and 6 cm) were the treatments investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…It was also noticed that the seeds sown at 0.2 mm depth had a significantly higher branch number of 12.0±2.0 compared to those sown at 0.4 and 0.6 mm depth with 9.0±1.0 and 8.0±2.0, respectively. Kibru et al (2015) and Chima et al (2017) reported that when the seeds are sown too deep, the germination of seeds are forced to push their tender shoots through the soil and the seedling may die or the seeds cannot germinate due to lack of oxygen, light, and temperature fluctuation. Depth of sowing did not influence the rate of biomass accumulation significantly and shoot biomass at 0.2, 0.4, and 0.6 mm was 0.561, 0.442, and 0.381 g, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…It was also noticed that the seeds sown at 0.2 mm depth had a significantly higher branch number of 12.0±2.0 compared to those sown at 0.4 and 0.6 mm depth with 9.0±1.0 and 8.0±2.0, respectively. Kibru et al (2015) and Chima et al (2017) reported that when the seeds are sown too deep, the germination of seeds are forced to push their tender shoots through the soil and the seedling may die or the seeds cannot germinate due to lack of oxygen, light, and temperature fluctuation. Depth of sowing did not influence the rate of biomass accumulation significantly and shoot biomass at 0.2, 0.4, and 0.6 mm was 0.561, 0.442, and 0.381 g, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, seeding depths played an important role in germination percentage, uniform germination and growth (Kibru et al, 2015 andChima et al, 2017) because when the seeds are sown too deep, the germination seeds are forced to push their tender shoots through the soil and the seedling may die or the seeds can not germinate due to lake oxygen, light and temperature fluctuation. Similarly, the seeds are sown too shallow, they may be dried and damaged by frost, birds and insects (Lal, 2003 andGholami et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…leucocephala seeds suffer from dormancy due to presence hard seed coat, so to enhance germination percentage, speed germination and uniform germination; they need special treatments to break the dormancy (Tadros et al, 2011). Depth of seed sowing is another important factor affecting the germination and consequently the seedling growth (Lal, 2003 andKibru et al, 2015).…”
Section: Introductionmentioning
confidence: 99%